2002
DOI: 10.1016/s1097-2765(02)00689-5
|View full text |Cite
|
Sign up to set email alerts
|

The Docking Protein FRS2α Controls a MAP Kinase-Mediated Negative Feedback Mechanism for Signaling by FGF Receptors

Abstract: The docking protein FRS2alpha functions as a major mediator of signaling by FGF and NGF receptors. Here we demonstrate that, in addition to tyrosine phosphorylation, FRS2alpha is phosphorylated by MAP kinase on multiple threonine residues in response to FGF stimulation or by insulin, EGF, and PDGF, extracellular stimuli that do not induce tyrosine phosphorylation of FRS2alpha. Prevention of FRS2alpha threonine phosphorylation results in constitutive tyrosine phosphorylation of FRS2alpha in unstimulated cells a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
132
2
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(145 citation statements)
references
References 40 publications
9
132
2
1
Order By: Relevance
“…It is well established that Frs2 represents not only the critical mediator of Erk activation in FGF signaling but also a site of negative feedback (56,57). Erk phosphorylates Frs2 on multiple threonine residues, leading to diminished recruitment of Grb2 and down-regulation of Ras/Erk activity (57).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well established that Frs2 represents not only the critical mediator of Erk activation in FGF signaling but also a site of negative feedback (56,57). Erk phosphorylates Frs2 on multiple threonine residues, leading to diminished recruitment of Grb2 and down-regulation of Ras/Erk activity (57).…”
Section: Discussionmentioning
confidence: 99%
“…Erk phosphorylates Frs2 on multiple threonine residues, leading to diminished recruitment of Grb2 and down-regulation of Ras/Erk activity (57). In RCS cells, FGF2 induced rapid, Erk-mediated phosphorylation of the entire Frs2 moiety.…”
Section: Discussionmentioning
confidence: 99%
“…1A and D bottom). Because FRS2 encodes the central adaptor protein downstream of FGFRs ( 15 ), FRS2-amplifi ed lung tumors may depend on signaling downstream of FGF receptors. Overall, FAPP dramatically reduced the number of genes (n Gene ) that occurred in broad amplifi cation peaks ( Fig.…”
Section: Research Articlementioning
confidence: 99%
“…FGFRs are activated via 22 different FGF ligands resulting in downstream FRS2 and extracellular signal-regulated kinase (ERK) phosphorylation ( 13 ); their signaling is modulated endogenously by multiple negative intrinsic feedback loops (15)(16)(17). Furthermore, alternative splicing of FGF receptors mediates different responses to FGF ligands in epithelial (expressing IIIb splice variants) and mesenchymal tissues (expressing IIIc splice variants) in development ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that Snts localize in the cell membrane through a myristyl anchor and interact with the FGFRs through a phosphotyrosine-binding (PTB) domain (Guy et al, 2002;Kouhara et al, 1997;Xu et al, 1998). Upon FGF stimulation, Snts are phosphorylated on multiple tyrosine residues to provide binding sites for the adaptor protein Grb2 and for the protein tyrosine phosphatase (PTP) Shp2 (Hadari et al, 1998;Kouhara et al, 1997), which in turn leads to the activation of the ERK arm of the mitogen activated protein kinase (MAPK) cascade or the phosphatidylinositol 3-kinase (PI3K) cascade and downstream changes in cell function or phenotype (Gotoh et al, 2004;Lamothe et al, 2004;Lax et al, 2002).…”
Section: Introductionmentioning
confidence: 99%